Long-Term Effect of Elevated CO2 on the Development and Nutrition Contents of the Pea Aphid (Acyrthosiphon pisum) - Li, Chunchun; Sun, Qian; Gou, Yuping; Zhang, Kexin; Zhang, Qiangyan; Zhou, Jing-Jiang; Liu, Changzhong (Frontiers in Physiology, 2021)
It is predicted that the current atmospheric CO2 level will be doubled by the end of this century. Here, we investigate the impacts of elevated CO2 (550 μL/L and 750 μL/L) on the development and nutrition status of the green pea aphid for six generations, which is longer than previous studies. All seven examined physiological parameters were not affected over 6 generations under the ambient CO2 level (380 μL/L). However, the elevated CO2 levels (550 μL/L and 750 μL/L) prolonged nymph duration, decreased adult longevity, female fecundity and protein content, and increased the contents of total lipid, soluble sugar and glycogen. There was a significant interaction between the effect of CO2 levels and the effect of generations on nymph duration, female fecundity and adult longevity. The elevated CO2 had immediate effects on the female fecundity and the contents of protein, lipid and soluble sugar, starting within F0 generation. The adult longevity decreased, and the glycogen content increased from the F1 generation. However, the significant effect on the nymph development was only observed after three generations. Our study indicates that the elevated CO2 levels first influence the reproduction, the nutrition and the energy supply, then initiate aphid emergency responses by shortening lifespan and increasing glucose metabolism, and finally result in the slow development under further persistent elevated CO2 conditions after three generations, possibly leading to population decline under elevated CO2 conditions. Our results will guide further field experiments under climate change conditions to evaluate the effects of elevated CO2 on the development of the pea aphids and other insects, and to predict the population dynamics of the green pea aphid.